Extending UTAUT2 to Explain Household Waste Management Behavior: The Moderating Role of Environmental Concern - Nani Irma Susanti; Jati Waskito; Kussudyarsana (Global Research Collaboration, 2026)
Household waste management represents a critical challenge alongside rapid urbanization in Indonesia. This study examines household waste management behavior by utilizing an extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. A quantitative explanatory approach was deployed through a survey of 100 household respondents in Joglo Subdistrict, Surakarta. Data analysis was executed via Partial Least Squares Structural Equation Modeling (PLS-SEM), through which behavioral intention was found to be significantly determined by all five primary constructs. The hierarchy of these predictors, from most to least dominant, is social influence, performance expectancy, effort expectancy, habit, and facilitating conditions. Additionally, a significant path was identified from behavioral intention to actual daily waste sorting practices. Regarding the moderating role of environmental concern, the results indicate partial moderation. While the links from facilitating conditions to intention and from intention to actual use are significantly amplified, the pathway between habit and intention remains unaffected. The limitations of this inquiry lie in its localized sample and cross sectional nature. Consequently, this research provides localized empirical insights into pro-environmental behavior models within a specific community context rather than broad theoretical generalizations. These preliminary findings offer a useful baseline reference for local authorities to design targeted waste management counseling and sustainable training programs in developing regions with similar socio cultural characteristics.